2020
DOI: 10.3389/fonc.2020.01585
|View full text |Cite
|
Sign up to set email alerts
|

The Survival and Prognostic Factors of Supratentorial Cortical Ependymomas: A Retrospective Cohort Study and Literature-Based Analysis

Abstract: Aim: Survival rates and prognostic factors of cortical ependymomas (CEs) remain elusive. This study aimed to perform a comprehensive analysis of prognostic factors, treatment, and outcomes for patients with CEs based on institutional and literature case series. Materials and Methods: Thirty patients with CEs from our department were included in this study. Furthermore, a systemic review of the literature yielded an additional 106 patients with CEs. Clinical data including patient age, sex, symptoms, tumor loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 62 publications
1
15
0
Order By: Relevance
“…In 2019, Matsumoto et al [ 15 ] reported their 8 cases and 84 cases previously reported CE cases. Their results were similar to those of Wang et al [ 14 ]. They performed Sanger sequencing of cDNA for finding C11orf95-RELA -fusion in 5 of their 8 cases that the test was available, and all 5 cases were fusion positive.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In 2019, Matsumoto et al [ 15 ] reported their 8 cases and 84 cases previously reported CE cases. Their results were similar to those of Wang et al [ 14 ]. They performed Sanger sequencing of cDNA for finding C11orf95-RELA -fusion in 5 of their 8 cases that the test was available, and all 5 cases were fusion positive.…”
Section: Discussionsupporting
confidence: 92%
“…In several literatures, CEs are defined as EPNs that are located in the cerebral cortex and have no connection to the ventricular lining and that account for only about 3.5% to 5.7% of all EPNs [ 2 3 14 15 ]. Especially, in some literatures like this case, it is called pure CEs to emphasize that they are limited only to the cerebral cortex [ 5 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations